Targeting DNA damage response in head and neck cancers through abrogation of cell cycle checkpoints. (3rd August 2021) - Molkentine, Jessica M.; Molkentine, David P.; Bridges, Kathleen A.; Xie, Tongxin; Yang, Liangpeng; Sheth, Aakash; Heffernan, Timothy P.; Clump, David A.; Faust, Alma Z.; Ferris, Robert L.; Myers, Jeffrey N.; Frederick, Mitchell J.; et al.
Abstract: Purpose: Head and neck cancers (HNSCC) are routinely treated with radiotherapy; however, normal tissue toxicity remains a concern. Therefore, it is important to validate treatment modalities combining molecularly targeted agents with radiotherapy to improve the therapeutic ratio. The aim of this study was to assess the ability of the PARP inhibitor niraparib (MK-4827) alone, or in combination with cell cycle checkpoint abrogating drugs targeting Chk1 (MK-8776) or Wee1 (MK-1775), to radiosensitize HNSCCs in the context of HPV status. Materials and methods: PARP1, PARP2, Chk1 or Wee1 shRNA constructs were analyzed from an in vivo shRNA screen of HNSCC xenografts comparing radiosensitization differences between HPV(+) and HPV(−) tumors. Radiosensitization by niraparib alone or in combination with MK-8776 or MK-1775 was assessed by clonogenic survival in HPV(−) and HPV(+) cells; and the role of p16 in determining response was explored. Relative expressions of DNA repair genes were compared by PCR array in HPV(+) and HPV(−) cells, and following siRNA-mediated knockdown of TRIP12 in HPV(−) cells. Results: In vivo shRNA screening showed a modest preferential radiosensitization by Wee1 and PARP2 in HPV(−) and Chk1 in HPV(+) tumor models. Niraparib alone enhanced the radiosensitivity of all HNSCC cell lines tested. However, HPV(−) cells were sensitized to a greater degree, as suggested by the shRNA screen. When combined with MK-8776 or MK-1775, radiosensitization was further enhanced in an HPV dependent manner with HPV(+) cells enhanced by MK-8776 and HPV(−) cells enhanced by MK-1775. A PCR array for DNA repair genes showed PARP and HR proteins BRCA1 and RAD51 were much lower in HPV(+) cells than in HPV(−). Similarly, directly knocking down p16-dependent TRIP12 decreased expression of these same genes. Overexpressing p16 decreased TRIP12 expression and increased radiosensitivity in HPV(−) HN5. However, while PARP inhibition led to significant radiosensitization in the control, it led to no further significant radiosensitization in p16 overexpressing cells. Forced p16 expression in HPV(−) HN5 increased accumulation in G1 and subG1 and limited progression to S phase, thus reducing effectiveness of PARP inhibition. Conclusions: Niraparib effectively radiosensitizes HNSCCs with a greater benefit seen in HPV(−). HPV status also plays a role in response to MK-8776 or MK-1775 when combined with niraparib due to differences in DNA repair mechanisms. This study suggests that using cell cycle abrogators in combination with PARP inhibitors may be a beneficial treatment option in HNSCC, but also emphasizes the importance of HPV status when considering effective treatment strategies.